PENILAIAN POTENSI OBJEK WISATA AIR TERJUN SARAY BRUNYAU DESA RIAM PIYANG KECAMATAN BUNUT HULU KABUPATEN KAPUAS HULU - Sarma Siahaan; Fahrid Mizwar; Reine Suci Wulandari (Jurnal Belantara, 2022)
Kapuas Hulu Regency is an area that has a variety of flora and fauna and has natural wealth and natural beauty that has the potential as a tourist attraction so that it must be developed, one of which is Saray Brunyau Waterfall in the forest area of ​​Riam Piyang Village, Bunut Hulu District, Kapuas Hulu Regency. Saray Brunyau Waterfall has the potential to be used as a tourist spot because the area has natural beauty and unspoiled scenery and has a natural panorama consisting of trees such as meranti trees (Shorea spp.), rengas trees (Gluta renghas, L), and many animals. wild animals such as monkeys, lempiau and other wildlife that adorn the waterfall area itself. Therefore Saray Brunyau Waterfall needs to be used as a place of research to get its potential value so that its feasibility can be known or developed into a tourist destination. The purpose of the study was to obtain the value of the potential attraction of Saray Brunyau Waterfall. The research method is a survey and direct observation in the field as well as conducting interviews with questionnaires using accidental sampling techniques to determine respondents and giving an assessment of each element and sub-element using the 2003 PHKA ODTWA assessment guideline. The elements assessed are a tourist attraction, accessibility, accommodation. , supporting infrastructure, regional security, and the availability of clean water. The results of the overall score get a total value of 2432/5 = 486.4 or fall into the classification category (B) meaning that it is quite potential to be developed into a tourist destination.